The Impact of Lung Function Parameters on Sleep Among Aboriginal Australians – A Polysomnography and Spirometry Relationship Study - Howarth T; Ben Saad H; Heraganahally SS (Dove Medical Press, 2023)
Timothy Howarth,1– 3 Helmi Ben Saad,4 Subash S Heraganahally1,5,6 1Darwin Respiratory and Sleep Health, Darwin Private Hospital, Darwin, Northern Territory, Australia; 2Department of Technical Physics, University of Eastern Finland, Kuopio, Finland; 3College of Health and Human Sciences, Charles Darwin University, Darwin, Northern Territory, Australia; 4Faculté de Médecine de Sousse, Hôpital Farhat HACHED de Sousse, Laboratoire de recherche “Insuffisance Cardiaque” (LR12SP09), Université de Sousse, Sousse, Tunisia; 5Department of Respiratory and Sleep Medicine, Royal Darwin Hospital, Darwin, Northern Territory, Australia; 6College of Medicine and Public Health, Flinders University, Adelaide, South Australia, AustraliaCorrespondence: Subash S Heraganahally, Email hssubhashcmc@hotmail.com; Subash.heraganahally@nt.gov.auBackground: Sleep disorders such as obstructive sleep apnoea (OSA) are known to overlap significantly with airway diseases in various populations. This study assessed the relationship between lung function parameters against polysomnography (PSG) and continuous positive airway pressure (CPAP) adherence data amongst an Aboriginal Australian population.Methods: Patients who undertook both a diagnostic PSG and spirometry were included. Restrictive, obstructive, and mixed impairments were assessed via global lung function initiative (GLI-2012, ATS/ERS) criteria/guidelines. PSG and CPAP data were evaluated between patients with or without spirometry impairments.Results: Of the total 771 patients, 248 had PSG and spirometry data available (52% female, 44% remote residents, 78% obese). The majority (89%) had OSA (51% severe), 95 (38%) were observed to have a restrictive impairment, and 31 (13%) had an obstructive or mixed impairment on spirometry. Compared to patients with no spirometric impairment, those with restrictive or obstructive/mixed impairments demonstrated significantly lower sleep efficiency (median 84% vs 79% and 78%), higher apnoea-hypopnea index (AHI) during rapid eye movement (REM) sleep ...